Satirical Language Style of Jombangan in The “Nano Bukan Permen” Youtube Channel - Laily, Laily Khoirotul Ummah; Eva Eri Dia (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2026)
Freedom of expression is a fundamental human right to convey opinions, particularly in conveying criticism through humor or language style. The language style often used is irony or satire, which has emerged as a phenomenon across social media platforms where harsh words are spoken but interspersed with jokes. The reason researcher chose the satirical language style in the Nano Bukan Permen YouTube channel is because of its use of satire through comedy or jokes, combined with the elements of Jombangan language that provide a distinctive local color. This study focuses on the forms and the functions of satire. The method used is descriptive qualitative as a means to identify the forms and functions of satire in the YouTube channel. Data identification was carried out through the following steps, those are, documentation or downloading data, transcribing, translating, selecting, coding, and classifying the data. The data source in this study is audiovisual material taken from the Nano Bukan Permen YouTube channel. The results of the study show that there are fifty-three utterances containing satire, consisting of twenty-five forms of Horatian satire, twenty-five forms of Juvenalian satire, and three forms of Menippean satire.